A historical perspective of allogeneic and autologous immunohaematopoietic stem cell transplantation in South Africa and a study of the non-haematologic consequences - Wood, Lucille (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.